Investigation of the Relationship Between Nursing Students’ Ethical Sensitivities and Care Behaviors - Yel, Pınar; Zengin, Neriman; Üçeriz, Aysenur Çetin (Makara Journal of Health Research, 2024)
Background: Care encompassing ethical and legal aspects is essential for nursing and involves actions that aim to improve individual well-being. In this study, we assessed the relationship between nursing students’ ethical sensitivity and care behaviors. Methods: This descriptive study included 191 students enrolled at a foundation university who consented to participate. Relevant data were gathered by using the Descriptive Information Form, Ethical Sensitivity Scale Adapted for Nursing Students, and Caring Behaviors Scale-24. Surveys were conducted face-to-face with the attending students and via Google Forms for the non-attending students. Results: The mean total score of the ethical sensitivity scale was 4.89 ± 0.60, indicating a moderate level, while the mean score for care behaviors was 5.32 ± 0.70, indicating a high level. Ethical sensitivity varied significantly by sex, and care behaviors varied according to sex and grade level (p < 0.05). A moderate positive correlation was found between ethical sensitivity and the total care behavior score (p < 0.05). Conclusions: Students had moderate ethical sensitivity and high care behaviors, with female students scoring higher in both areas compared to male students. In addition, higher ethical sensitivity levels were correlated with increased care behaviors.